Association between XRCC1 exon 10 (Arg399Gln) gene polymorphism and micronucleus as a predictor of DNA damage among radiation workers - HARRY NUGROHO EKO SURNIYANTORO; YANTI LUSIYANTI; TUR RAHARDJO; SITI NURHAYATI; DEVITA TETRIANA (Biodiversitas Journal of Biological Diversity, 2018)
Surniyantoro HNE, Lusiyanti Y, Rahardjo T, Nurhayati S, Tetriana D. 2018. Association between XRCC1 exon 10 (Arg399Gln) gene polymorphism and micronucleus as a predictor of DNA damage among radiation workers. Biodiversitas 19: 1676-1682. This study was aimed to examine the association between XRCC1 exon 10 gene polymorphism and micronucleus frequencies in radiation workers and their relation to the confounding factors. This study involved 37 radiation workers and 37 controls from several hospitals in Indonesia. Genotyping of X-ray cross-complementing group 1 (XRCC1) exon 10 gene polymorphism and micronucleus assay were performed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and Cytokinesis-Block Micronucleus assay (CBMN assay), respectively. The results indicated that MN frequencies were not significantly higher in the exposed workers than in controls (20.46±6.42 versus 16.89 ±9.72; P=0.07). The micronucleus frequencies of radiation workers with mutant genotype showed not significantly higher than controls in the same genotypes (22±6.64 versus 11.75 ± 8.13; P=0.11). The confounding factors, like age, years of employment and equivalent doses were significantly associated with micronucleus frequencies (P<0.05). The equivalent dose has a significantly positive correlation with micronucleus frequencies among radiation workers, increasing the MN frequencies by 16.3 per 1 mSv of equivalent dose (P=0.001). The genetic polymorphism of XRCC1 gene exon 10 demonstrated no association with the extent of DNA damage in the hospital radiation workers. The MN frequencies were strongly associated with age, equivalent dose and years of employment.